Acceptance of The Kangaroo Care Method by Mothers in Rural Area - Rulina Suradi; lmral Chair; Ridwan M. Thaha (Indonesian Pediatric Society, 1998)
We evaluate the acceptance of Kangaroo Care Method (KCM) among ruralmother giving birth to LBW infants in the rural health centers of 3 provinces in Indonesia, from June 1 through November 30, 1997. All mothers giving birth to LBW infants (birth weight 1500-2500 grams) seen by the rural team on the first day with no morbidity requiring hospitalisation were included in this study. One hundred and sixteen mothers fulfilled the criteria, most of them (62.1%) were between 20-29 years of age. Birthweight between 2000-2500 grams was found in 86.2%, of infants, and 67.3% are fullterm small for date babies. Most respondents accepted the KCM because they were interested in a new and practical method showed by the midwife; 11.8% accepted it because it resembled the local habit. All the mothers in the three locations had a positive perception on the benefit of KCM; 90% found that their babies were more calm, 92.7%, said that their babies slept more and 85.4% said that their babies breastfed more often. As for their feelings, everyone said that they felt happy. As many as 86.4% of mothers practiced the use of KCM during the 28 days, but only 40% of them used them for a total of more than 5 hours a day. More than 80% of the mothers had support from the family and more than 60% had a substitute for the KCM. We conclude that KCM was feasible and acceptable among the rural community.